Effect of Parental Migration Background on Childhood Nutrition, Physical Activity, and Body Mass Index - Mohsen Besharat Pour; Anna Bergström; Matteo Bottai; Inger Kull; Magnus Wickman; Niclas Håkansson; Alicja Wolk; Tahereh Moradi (Journal of Obesity)
Background. Poor nutrition, lack of physical activity, and obesity in children have important public health implications but, to date, their effects have not been studied in the growing population of children in Sweden with immigrant parents. Methods. We estimated the association between parental migration background and nutrition, physical activity, and weight in 8-year-old children born in Stockholm between 1994 and 1996 of immigrants and Swedish parents (n=2589). Data were collected through clinical examination and questionnaires filled out by parents. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated using multivariable logistic regression. Results. Children of immigrants complied more closely with Nordic Nutrition Recommendations compared with those of Swedes (OR = 1.35, 95% CI 1.11–1.64). They had higher intake of dietary fibre, vitamins C, B6, and E, folic acid, and polyunsaturated fatty acids (omega-3 and omega-6) reflecting higher consumption of foods of plant origin, but lower intake of vitamins A and D, calcium, and iron reflecting lower consumption of dairy products. Children of immigrants had higher intake of sucrose reflecting higher consumption of sugar and sweets. Furthermore, these children had a higher risk of having low physical activity (OR = 1.31, 95% CI 1.06–1.62) and being overweight (OR = 1.33, 95% CI 1.06–1.65) compared with children of Swedish parents. The odds of having low physical activity and being overweight were even higher in children whose parents were both immigrants. A low level of parental education was associated with increased risk of low physical activity regardless of immigration background. Conclusions. Culturally appropriate tools to capture the diverse range of ethnic foods and other lifestyle habits are needed. Healthcare professionals should be aware of the low levels of physical activity, increased weight, and lack of consumption of some important vitamins among children of immigrants.